Entrepreneurial capabilities of successful firms: a study of small and medium-scale equipment manufacturers in Nairobi, Kenya. (22nd December 2020) - Upadhyaya, Radha; McCormick, Dorothy
What capabilities have enabled successful entrepreneurs in developing countries to overcome the challenges of their environment? To answer this question, this study explored the entrepreneurial capabilities of a group of 19 successful metalworking firms manufacturing food processing equipment in Nairobi. Theoretically, the study is rooted in the resource-based view of the firm. The study's research design followed a mixed methods approach. The quantitative survey showed that the majority of firms attribute their success to the vision and leadership of the entrepreneur. The qualitative case study interviews highlighted several capabilities including: capability to envision and lead into the future; resilience; flexibility and adaptability; ability to hire and retain skilled workers; and the ability to interact constructively with customers. The paper shows that firms' perspectives on capabilities emphasise the 'softer' capabilities of entrepreneurs, which reside mainly in the knowledge-based strand of the resource-based view.